Reinventing the medical librarian. - Anderson, R K (1989)
The caliber of the librarian is a health sciences library's most important resource. This paper explores factors which have influenced who has, or who has not, entered the profession of medical librarianship, and discusses several attributes which the author considers critical for restructuring the profession to meet current and future needs.